Pilot's handbook of aeronautical knowledge (Federal Aviation Administration, 2016)
The Pilot's Handbook of Aeronautical Knowledge provides basic knowledge that is essential for pilots. This handbook introduces pilots to the broad spectrum of knowledge that will be needed as they progress in their pilot training. Most of the knowledge areas required and applicable to FAA pilot certification are presented inside this book. This handbook is useful to beginning pilots, as well as those pursuing more advanced pilot certificates. It is also an invaluable source of reference material beneficial to pilots who wish to improve their aeronautical knowledge.